A diagnostic test for malnutrition in adults: mid-upper arm circumference towards body mass index: A literature review - Fathiyyatul Khaira; Fiastuti Witjaksono; Diyah Eka Andayani (Indonesian Nutrition Association, 2021)
Body mass index is commonly used for detecting malnutrition. At certain conditions, body mass index cannot be measured, so mid-upper arm circumference can be an alternative measurement for detecting malnutrition. Several studies have proposed the cut-off point of mid-upper arm circumference in adults along with its sensitivity, specificity, and area under the ROC curve (AUC). This article aims to describe the diagnostic test for malnutrition using the upper arm circumference in adults and summarize the results of the related studies.